ANALISIS FAKTOR-FAKTOR YANG MENYEBABKAN PENGEMUDI TERLIBAT DALAM KECELAKAAN LALU LINTAS DI KOTA YOGYAKARTA - Herman Wahyu Dwi Maelana; Prihartarto Eko Wibowo (ALBAMA: JURNAL BISNIS ADMINISTRASI DAN MANAJEMEN, 2023)
A traffic accident is an unexpected event and an event that is not caused by an element of intent. Traffic accidents can cause harm to the driver himself or to other people by causing loss of life or material loss. This study aimed to determine the factors that caused drivers to be involved in traffic accidents in the City of Yogyakarta. This research is a quantitative research type. The data sources used were primary data, in the form of interviews and secondary data in the form of existing data at the Yogyakarta City Transportation Agency. Data collection techniques were carried out by literature study, documentation and interviews. The data population and data samples were 1520 from 2019-2021. The analysis was performed using diagram analysis and univariate analysis. There has been a decrease in the number of traffic accidents caused by driver factors in the city of Yogyakarta from 2019 to 2021. With the percentage of Disorganized 37.1%, Speed Limit 33.6%, Inattentive 14.9%, Tired 10.3%, Drowsiness 3.6%, Effect of Alcohol 0.3% and sickness 0.2%.